La costruzione sociale dell'innovazione Economia, società e territorio - Trigilia, Carlo (Pluriverso - Quaderni della Biblioteca del Polo Universitario di Prato, 2007)
In contemporary economics the social and relational dimension of innovation comes to predominate over the corporate aspect. Innovative processes mature not only within the confines of the enterprise, but increasingly through the formal and informal relations that the companies develop between them, and with the suppliers, the customers and the structures for education and research. This connotation of interaction and dialogue is accompanied by a new local embedding of the innovative activities: it is within the territory, through direct interaction often of an informal nature, that tacit knowledge is developed as a crucial resource for innovation. It is on this process of innovation that the essays in this volume focus, bringing to light the consequences that derive for the mapping of policies aimed at sustaining innovative initiatives.